The Rational Programmer: Investigating Programming Language Pragmatics. - Dimoulas, Christos; Felleisen, Matthias (Communications of the ACM, 2025)
This article presents the development of the rational programmer, which incorporates pragmatics into developing and updating programming languages. Topics include typed and untyped programming languages, run-time checks and type mismatches. The article presents how the rational programmer works, what it delivers, and what it is not- with an emphasis on the need for complementary human studies.